Uji Aktivitas Antibakteri Ekstrak Buah Tin (Ficus carica L.) Terhadap Bakteri Streptococcus pneumoniae - Salsabila, Lu’lu Luqyana Amirah; Syamsu, Rachmat Faisal; Utami, Dian Fahmi; Sodiqah, Yani; Anggita, Dwi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Streptococcus pneumoniae (pneumococcus) is a normal flora in the respiratory tract that can mutate into pathogenic bacteria that cause Invasive Pneumococcal Disease (IPD) such as pneumonia. The high prevalence of pneumonia causes antibiotics to be the appropriate therapy to treat cases of infection by bacteria. However, the use of antibiotics that are not indicated can lead to other health problems, namely antibiotic resistance. One of the efforts that can be made to reduce the rate of antibiotic resistance is the utilization of natural-based antibiotics. One of the plants that has potential as a natural antibiotic is Tin fruit (Ficus carica L.) which is thought to be due to the presence of antibacterial compounds in it, namely tannins, phenols, and flavonoids. The specialty of Tin fruit is also mentioned in the Qur'an surah At-Tiin verse 1 which means "By (the fruit) Tin and (the fruit) Olive".  To determine the antibacterial activity of Tin fruit (Ficus carica L.) against Streptococcus pneumoniae bacteria. The research conducted was a true experimental post test study using the disc diffusion method (Kirby Bauer method) to see the effectiveness of Tin fruit extract (Ficus carica L.) in inhibiting the growth of Streptococcus pneumoniae bacteria. Tin fruit extract (Ficus carica L.) with a concentration of 50% is resistant to Streptococcus pneumoniae bacteria with an inhibition diameter of 4.35 mm. While the 100% concentration is sensitive in inhibiting the growth of Streptococcus pneumoniae bacteria with an inhibition diameter of 19.45 mm. Tin fruit extract (Ficus carica L.) has antibacterial activity in inhibiting the growth of Streptococcus pneumoniae bacteria.